Vine Killers and time of application on seed potato cv. Radosa production - Souza, Zilmar da Silva (Pesquisa Agropecuaria Brasileira, 1991)
An experiment was carry out at São Joaquim Experimental Station, São Joaquim, SC, Brazil, to evaluate the effects of chemicals vine killers on seed potato production (Solanum tuberosum L.), cv. Radosa. All treatments were applied on three times: 40, 50 and 60 days after emergence. The treatments were following: 0,3 1/ha, 0,6 1/ha and 1,2 1/ha paraquat; 0,6 1/ha diquat; 2,5 1/ha dinoseb; 13 kg/ha DNOC; 0,5 l/ha bromoxinyl, control I; cut of vines + 0,3 1/ha paraquat and control II. Doses of 0,6 1/ha paraquat or diquat were enough for total drying vine about seven days after application. The dinoseb, DNOC and bromoxinyl were not effective. The removal of vines by cut before application of paraquat make the operation and action of vine killer become easy. The production of seed tuber sizes II + III were higher about 40 days after application, and decreased with delay of time of application, while the production of seed tuber sizes I + II + III + IV increased in the same time. The browing internal vascular discoloration in tuber seed were not observable.
Keywords: Solanum tuberosum; seed tuber; paraquat; diquat; dinoseb